EFFECT OF MACROECONOMIC VARIABLES ON JAKARTA ISLAMIC INDEX: EVIDENCE THE GLOBAL TRADE WAR PHENOMENON - Rizaldi Yusfiarto; Galuh Tri Pambekti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2019)
The development of investment in the Islamic capital market, especially the Jakarta Islamic Index (JII) as a percentage, experienced significant development, and it is because the Islamic index uses Islamic principles and procedures. The phenomenon of the trade war between the United States and China has an impact on macro variable fluctuations, which can empirically influence the growth of the sharia index. For this reason, this study aims to analyze the impact of change due to the trade war sentiment. Macroeconomic variables used in this study are the USD / IDR exchange rate, the CNY / IDR exchange rate, inflation, Crude oil WTI, and ICP Crude oil. This study uses a vector autoregression analysis (VAR) technique. Stationarity test using the Augmented Dickey-Fuller test (ADF test) and the Philips-Perron Test. The analysis shows that there is an influence between changes in exchange rates and changes in crude oil prices on the return of the Jakarta Islamic Index (JII) in the range of research data periods used.